2020
DOI: 10.20944/preprints202009.0410.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significant baseflow reduction in the Sao Francisco River Basin

Abstract: Water scarcity is a key challenge to global development. In Brazil, the Sao Francisco River Basin (SFB) has experienced water scarcity problems because of decreasing streamflow and increasing demands from multiple sectors. However, the drivers of decreased streamflow, particularly the potential role of surface-groundwater interaction, have not been yet investigated. Here, we assess long-term trends in baseflow, quickflow, and streamflow of the SFB during 1980–2015 and constrain the most likely driver… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
1
9
0
2
Order By: Relevance
“…This situation is aggravated by the long‐term conversion of natural vegetation to different agricultural land uses (e.g., sugarcane, soybean, and corn), which have been responsible for more than half of the national grain production (Spera, 2017) mainly in the Cerrado. Furthermore, the increase in irrigated areas for food production in the Cerrado and Caatinga biomes has been recently related to an increase in evapotranspiration and baseflow reduction in these regions (Oliveira et al, 2019; Lucas et al, 2020). The impacts of land use and land cover change (LULCC) on the catchments' water fluxes are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is aggravated by the long‐term conversion of natural vegetation to different agricultural land uses (e.g., sugarcane, soybean, and corn), which have been responsible for more than half of the national grain production (Spera, 2017) mainly in the Cerrado. Furthermore, the increase in irrigated areas for food production in the Cerrado and Caatinga biomes has been recently related to an increase in evapotranspiration and baseflow reduction in these regions (Oliveira et al, 2019; Lucas et al, 2020). The impacts of land use and land cover change (LULCC) on the catchments' water fluxes are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Lucas et al. (2021) suggested streamflow depletion was leading to a decline in baseflow due to a spatial agreement between declining baseflow trends, increasing evapotranspiration trends, and irrigated agricultural land. In contrast to statistical assessments, statistical models applied to streamflow depletion estimation typically attempt to quantify some relationship between groundwater pumping and long‐term changes in streamflow and/or baseflow, often as one of several predictors.…”
Section: Methods Used For Quantifying Streamflow Depletionmentioning
confidence: 99%
“…For example, Kustu et al (2010) observed a spatial match between negative trends in groundwater levels and streamflow across the U.S. High Plains Aquifer and inferred a connection between the two based on the absence of potential explanatory precipitation trends, and Juracek (2015) compared numerous gages in southern Kansas and found significant decreasing streamflow trends in basins with the greatest groundwater level decline and a lack of precipitation trends, which together suggested that streamflow depletion was the cause of observed streamflow trends. In Brazil, Lucas et al (2021) suggested streamflow depletion was leading to a decline in baseflow due to a spatial agreement between declining baseflow trends, increasing evapotranspiration trends, and irrigated agricultural land. In contrast to statistical assessments, statistical models applied to streamflow depletion estimation typically attempt to quantify some relationship between groundwater pumping and long-term changes in streamflow and/or baseflow, often as one of several predictors.…”
Section: Statistical Assessments and Modelsmentioning
confidence: 99%
“…High Plains Aquifer and inferred a connection between the two based on the absence of potential explanatory precipitation trends, and Juracek (2015) compared numerous gages in southern Kansas and found significant decreasing streamflow trends in basins with the greatest groundwater level decline and a lack of precipitation trends, which together suggested that streamflow depletion was the cause of observed streamflow trends. In Brazil, Lucas et al (2021) suggested streamflow depletion was leading to a decline in baseflow due to a spatial agreement between declining baseflow trends, increasing evapotranspiration trends, and irrigated agricultural land. In contrast to statistical assessments, statistical models applied to streamflow depletion estimation typically attempt to quantify some relationship between groundwater pumping and long-term changes in streamflow and/or baseflow, often as one of several predictors.…”
Section: Statistical Assessments and Modelsmentioning
confidence: 99%